Atropine use may lead to post-operative respiratory acidosis in neonates receiving ductal ligation: A retrospective cohort study - Szu-Ling Chang; Wen-Li Lin; Chien-Hsiang Weng; Shye-Jao Wu; Hsin-Jung Tsai; Shwu-Meei Wang; Chun-Chih Peng; Jui-Hsing Chang (Elsevier, 2018)
Background: Patent ductus arteriosus (PDA) is one of the most common cardiac conditions in preterm infants. Closure of the PDA in symptomatic patients can be achieved medically or surgically. Atropine is commonly administered in general anesthesia as a premedication in this age group but with limited evidence addressing the effect of its use. Our study examined the association of the use of atropine as a premedication in PDA ligation and the risk of post-operative respiratory complications. Methods: This retrospective cohort study included 150 newborns who have failed medical treatment for PDA and received PDA ligation during 2008-2012 in a single tertiary medical center. Ninety-two of them (61.3%) received atropine as premedication for general anesthesia while 58 (38.7%) did not. Post-operative respiratory condition, the need of cardiopulmonary resuscitation and the presence of bradycardia were measured. Results: Patients with atropine use were associated with increased odds of respiratory acidosis in both univariate analysis (22.9% vs 7.3%; OR = 3.785, 95% CI = 1.211-11.826, p = 0.022) and multivariate analysis (OR = 4.030, 95% CI = 1.230-13.202, p = 0.021), with an even higher odds of respiratory acidosis in patients receiving both atropine and ketamine. Conclusion: The use of atropine as premedication in general anesthesia for neonatal PDA ligation is associated with higher risk of respiratory acidosis, which worsens with the combined use of ketamine. Key Words: respiratory acidosis, atropine, patent ductus arteriosus, ketamine